Peran Jurnalis Investigatif dalam Mengungkap Kasus Narkoba: Analisis Tantangan dan Hambatan Investigasi Jurnalisme - Ahmad Salman Farid; Muhammad Ardiansyah (MUKASI: Jurnal Ilmu Komunikasi, 2023)
This study analyzes the role of investigative journalists in exposing drug cases through investigative journalism. Investigative journalism has the potential to uncover hidden drug trafficking practices, highlight the roles of relevant actors, and provide a better understanding of drug flows and their impact on society. Using a qualitative analysis method, this research examines cases of journalism investigations that have succeeded in uncovering drug trafficking practices. Data is collected through investigative journalism articles, investigative reports, and interviews with investigative journalists. This study analyzes the strategies, techniques and approaches used by journalists in exposing drug cases. The results of this study reveal that journalists act as public watchdogs who raise drug issues, increase public awareness, and compel the government to take action. The main roles of journalists include gathering evidence, interviewing sources, conducting analysis and research, uncovering facts, and reporting and communicating their findings. This research provides a better understanding of the important role of investigative journalists in exposing drug trafficking practices and contributes to improving efforts to prevent and deal with drugs globally.